Modified Technology Acceptance Model Forecasts Canva Usage By Teachers: Model Penerimaan Teknologi Modifikasi Memprakirakan Penggunaan Canva Oleh Guru - Gagus Wertika Yasa; Masduki Zakarijah (Academia Open, 2026)
General Background Digital transformation fundamentally shifts educational paradigms, requiring educators to adopt interactive visual learning platforms. Specific Background Yayasan Insan Mandiri Denpasar mandates specific design software for 178 educators across Lombok and Sumbawa, yet adoption remains inconsistent despite institutional directives. Knowledge Gap Traditional technology adoption frameworks fail to adequately explain educational software integration because they overlook how technical features align with pedagogical demands. Aims This study evaluates platform acceptance among educators using a modified theoretical framework incorporating compatibility with instructional requirements. Results Partial Least Squares Structural Equation Modeling reveals that perceived usefulness and compatibility with instructional requirements positively determine behavioral intention. Conversely, perceived ease of operation lacks a direct relationship with intention, operating solely as an indirect determinant through instructional compatibility. Novelty This research isolates pedagogical compatibility as a crucial mediating variable that bridges the gap between operational simplicity and sustained technological integration. Implications Educational institutions must design training programs that prioritize pedagogical integration and practical utility over basic technical navigation. Highlights Perceived usefulness and instructional compatibility directly dictate the behavioral intention of educators to adopt digital platforms. Perceived ease of operation does not directly govern the behavioral intention for instructional purposes. Instructional compatibility successfully mediates the relationship between operational simplicity, perceived utility, and sustained software integration. Keywords Partial Least Squares; Instructional Needs Compatibility; Behavioral Intention; Educational Software Adoption; Structural Equation Modeling